IMPLEMENTASI MODEL PROJECT-BASED LEARNING UNTUK MEMFASILITASI KEMAMPUAN LITERASI SAINS SISWA SD - Florentina Vanessa Kalista Kaut; Totok Victor Didik Saputro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research that will be studied is to see the improvement of elementary school students' scientific literacy skills, the importance of scientific literacy and the challenges in its development at the elementary school level, various approaches and innovative learning models continue to be explored. One of the learning models that is considered potential to facilitate scientific literacy skills is Project Based Learning (PjBL). PJBL is a student-centered learning approach, where students work collaboratively on real projects that are relevant to their lives. Through PjBL, students have the opportunity to conduct in-depth investigations, design solutions, collect and analyze data, and communicate their formulations. This process directly trains various aspects of scientific literacy, from formulating scientific questions to evaluating information and drawing conclusions based on evidence. This study aims to analyze the scientific literacy skills of elementary school students by implementing the Project Based Learning (PjBL) model. This study used research subjects were students of SDN 07 Sebalo, there were 20 students who took part in science learning, data was collected using a quantitative descriptive approach to the test instrument. The test instrument was used to measure the scientific literacy skills of elementary school students, the data analysis technique used descriptive statistics. The results of the study stated that students' scientific literacy skills increased by using the Classroom Action Research (CAR) method, with 2 cycle stages, from the collection of data analysis, the average student test score reached 73.5. The implementation of the Project Based Learning (PjBL) model has a very significant impact on the development of elementary school students' literacy skills. This Project Based Learning